Single phase ZnV2O6 nanorods with excellent visible light photodetection capability - Kim, Kyung Min; Cho, Hyeon Ho; Yu, Hak Ki; Kim, Myung Hwa (Journal of Alloys and Compounds, 2023)
We report a facile synthetic route for the growth of single phase ZnV2O6 nanorods via a simple acid–base reaction of the Lewis acid forms of ZnCl2 and VCl3 with NaOH in an aqueous solution followed by the thermal treatment of the resulting metal hydroxides on a SiO2 substrate in air. The as-grown ZnV2O6 nanorods exhibited a well-defined rectangular cross-section with a width of approximately 300–350 nm and thickness of 100–150 nm, and they extended in random directions up to a length of 3 µm. The as-grown ZnV2O6 nanorods possessed a single-phase monoclinic brannerite-type structure, as determined via X-ray diffraction, X-ray photoelectron spectroscopy, and Raman spectroscopic investigations. The synthesized ZnV2O6 sample exhibited a band gap of ∼2.06 eV and excellent photodetection properties in the visible light region of 635 nm, which is the band-edge wavelength. The new ZnV2O6 synthetic method proposed in this report could be used to develop various photocatalysts and energy conversion materials in the future.
Keywords: Acid-base reactions; As-grown; Band-edge wavelength; Bands edges; Nanostructure synthesis; Photo detection; Single phasis; Synthetic routes; Visible light; Visible light photodetector; Acid–base reaction; Band-edge wavelength; Nanostructure synthesis; Visible light photodetector; ZnV2O6